Tagus estuary salt marshes feedback to sea level rise over a 40-year period: Insights from the application of geochemical indices - Duarte, B. (2013)
Sea level rise (SLR) has been evaluated using data acquired from two Tagus estuary salt marshes. Sediment accumulation rates over a 40-year study period were determined using 137Cs along with an evaluation of several geochemical indices and ratios as proxies of the mechisms underlying these SAR variations. Correlating SLR data from 1963 to 2001 with the sediment accretion rates (SARs) an inverse pattern of interaction was observed, with lower SAR associated to periods of higher mean sea level (MSL) heights. This pointed out to an erosion effect of the salt marsh during higher tidal flooding. Although SLR apparently slows down SAR, it still presents a positive balance with SLR, similar to that identified in most mesotidal estuaries. The geochemical analysis of sediments and chemical alteration index (CAI) also suggest that the major processes inherent to the SAR vary inversely, being mostly based by physical disturbances. Geochemical ratio-based indices showed that both salt marshes presented enhanced highenergy transport driven inputs of sediments, although in Pancas salt marsh there is a slight evidence of chemical weathering of the sediments. Anthropogenic contamination of the sediments by heavy metals was identified and has been decreasing from 1963 to 2001, mostly linked to a marked reduction of industrial activities in some areas surrounding the Tagus estuary, rather than the sedimentary history of the estuary.